2021
DOI: 10.1177/17411432211015227
|View full text |Cite
|
Sign up to set email alerts
|

Principal leadership practices, professional learning communities, and teacher commitment in Hong Kong kindergartens: A multilevel SEM analysis

Abstract: In response to the needs for kindergarten principals to foster teachers’ capacities and commitment, this study examined the relationships between professional learning communities, principal leadership practices, and teacher commitment to kindergartens among 2106 teachers from 153 Hong Kong kindergartens, analyzing by using multilevel structural equation modeling. The result showed that principal leadership practices facilitated the development of professional learning communities at school and teacher levels,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 67 publications
(228 reference statements)
2
10
0
Order By: Relevance
“…Unlike previous studies that examined the relationship between principal leadership and PLCs from teachers' perspective, this study adopted principals' perspective to explore the effect of transformational leadership on PLCs. Results provide empirical evidence on the crucial role of transformational leadership in PLCs in China [29], and lend credence to findings of studies from teachers' perspectives that leadership matters a lot to the practice of PLCs [17,18,[21][22][23].…”
Section: Effect Of Transformational Leadership On Plc Componentssupporting
confidence: 60%
See 1 more Smart Citation
“…Unlike previous studies that examined the relationship between principal leadership and PLCs from teachers' perspective, this study adopted principals' perspective to explore the effect of transformational leadership on PLCs. Results provide empirical evidence on the crucial role of transformational leadership in PLCs in China [29], and lend credence to findings of studies from teachers' perspectives that leadership matters a lot to the practice of PLCs [17,18,[21][22][23].…”
Section: Effect Of Transformational Leadership On Plc Componentssupporting
confidence: 60%
“…Furthermore, research devoted considerable attention on how to establish effective PLCs. Various stages for the development of PLCs were identified [16], and the crucial role of principal leadership in implementing PLCs and promoting professional development is consistently highlighted [17][18][19]. In addition, studies have explored the effects of PLCs on teachers and students.…”
Section: Introductionmentioning
confidence: 99%
“…The principal will regularly control the tasks given to their respective homerooms. This is in accordance with the opinion of To et al, (2021) that it is very important for the principal to supervise teacher activities (2) teachers feel unappreciated by students; principals, students, 11K coordinators, and homeroom teachers make joint rules regarding discipline in class, and whoever violates these rules will be penalized according to the rules that have been made, such as students who are not polite to teachers, they will be given guidance and if they still repeat then people will be punished. student parents will be called.…”
Section: Teachers Often Give Notes To Studentssupporting
confidence: 93%
“…Guided by research on professional learning communities (PLCs), education systems accept the value of engaging teachers to work collaboratively for teacher knowledge, skill, beliefs, practice, and student learning outcomes (Doğan and Adams, 2018;Lomos et al, 2011;Zheng et al, 2021). Notably, these research findings have emerged not only in Western societies (Admiraal et al, 2021;Park et al, 2019), but also in East Asia (Liu and Yin, 2022;To et al, 2021;Yin et al, 2019;Zheng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of PLCs for enhancing teachers’ practices as well as student achievement (Lomos et al, 2011; Ronfeldt et al, 2015), how supportive conditions promote the enactment of PLCs has attracted increasing interest from researchers (Bryk et al, 1999; Gray et al, 2016; Qian and Walker, 2021). School leadership is one important factor that supports the enactment of PLCs (Hairon and Tan, 2017; Ho et al, 2020; Qian and Walker, 2021; To et al, 2021). Studies have found that leadership practices are associated with instructional leadership (Vanblaere and Devos, 2016; Wang, 2016; Zheng et al, 2019) and transformational leadership (i.e.…”
Section: Introductionmentioning
confidence: 99%